Coevolution of HIV-1 and broadly neutralizing antibodies. Issue 4 (July 2019) - Doria-Rose, Nicole A.; Landais, Elise
Abstract : Purpose of review: Exploring the molecular details of the coevolution of HIV-1 Envelope with broadly neutralizing antibodies (bNAbs) in infected individuals over time provides insights for vaccine design. Since mid-2017, the number of individuals described in such publications has nearly tripled. New publications have extended such studies to new epitopes on Env and provided more detail on previously known sites. Recent findings: Studies of two donors – one of them an infant, the other with three lineages targeting the same site – has deepened our understanding of V3-glycan-directed lineages. A V2-apex-directed lineage showed remarkable similarity to a lineage from a previously described donor, revealing general principles for this class of bNAbs. Understanding development of CD4 binding site antibodies has been enriched by the study of a VRC01-class lineage. Finally, the membrane-proximal external region is a new addition to the set of epitopes studied in this manner, with early development events explored in a study of three lineages from a single donor. Summary: These studies provide templates for immunogen design to elicit bNAbs against a widened set of epitopes, generating new directions in the quest for an HIV vaccine.